A Contrastive Study of the Voice Onset Time (VOT) in English and Arabic Languages - Mansoor Mahmood, Rafida (Al-Adab Journal, 2018)
The signal sound contains many different features. One of these features is voice onset time henceforth )VOT) and this feature refers to the ways different people of different languages have been distinguished by the way they articulate stop consonants of their own language. This feature (VOT) can be utilized by the human auditory system to distinguish between voiced and devoiced stops such as /p/ and /b /in English, /t/ and /t?/ Arabic. The study is contributed into five sections:- Section One is introductory, which contains the introduction, the problem, the hypothesis, the aim, the limitation and the value of the study. Section Two shows the definitions and types of VOT: positive, negative, zero VOT and role of VOT. Section Three deals with the measurement and categorical perception of VOT, these ways of measurements are spectrograms, waveform and lagtime. Section Four investigates the VOT of two languages, Arabic and English in details with a comparison between these two languages. It ends with a number of conclusions. One of these conclusions is that Arabic VOT is different from English VOT and this approved the hypothesis.